The progress of global financial transparency: Evidence from the financial secrecy index 2009-2018 - Petr Janský; Miroslav Palanský (Charles University in Prague, Institute of Economic Studies (IES), 2019)
While financial secrecy has recently risen on the agenda of policy makers and scholars alike, much remains unknown about its development since the global financial crisis. To show how financial secrecy evolved over time on average, by category, and across countries, we combine the five Financial Secrecy Index editions from 2009 to 2018 to create a financial secrecy panel data set. We present four main findings. First, financial secrecy has decreased on average - i.e. that financial transparency has improved - by at least 2-9% between 2011 and 2018. Second, most of the observed improvement comes from international standards and cooperation, one of four key financial secrecy areas recognized by the Financial Secrecy Index. Third, we observe a convergence across countries between 2011 and 2018 - many of the most secretive have become less so while the opposite is true of some formerly less secretive countries. For example, the Seychelles are now only slightly more secretive than the Netherlands. Fourth, we find that changes in contributions to global financial secrecy over time are not tied to geographical regions and that it is thus worth studying changes at the individual country-level. For example, we find that the United Arab Emirates, the Netherlands and Malta have become substantially more important providers of financial secrecy, though they are still less important than the current leaders, i.e. Switzerland, the United States and the Cayman Islands. Having documented changes in financial secrecy over the past decade, we conclude with how the data set may be used as a tool for studying and perhaps even curbing financial secrecy - a policy objective which has thus far been only moderately met.
Keywords: F36; F65; G28; H26; H87; 330; Offshore finance; financial transparency; financial secrecy; secrecy jurisdictions; tax havens